Nicotinamide Riboside and Metformin Ameliorate Mitophagy Defect in Induced Pluripotent Stem Cell-Derived Astrocytes With POLG Mutations - Chen, Anbin; Kristiansen, Cecilie Katrin; Hong, Yu; Kianian, Atefeh; Fang, Evandro Fei; Sullivan, Gareth John; Wang, Jian; Li, Xingang; Bindoff, Laurence A.; Liang, Kristina Xiao (Frontiers in Cell and Developmental Biology, 2021)
Mitophagy specifically recognizes and removes damaged or superfluous mitochondria to maintain mitochondrial homeostasis and proper neuronal function. Defective mitophagy and the resulting accumulation of damaged mitochondria occur in several neurodegenerative diseases. Previously, we showed mitochondrial dysfunction in astrocytes with POLG mutations and here, we examined how POLG mutations affect mitophagy in astrocytes and how this can be ameliorated pharmacologically. Using induced pluripotent stem cell (iPSC)-derived astrocytes carrying POLG mutations, we found downregulation of mitophagy/autophagy-related genes using RNA sequencing-based KEGG metabolic pathway analysis. We confirmed a deficit in mitochondrial autophagosome formation under exogenous stress conditions and downregulation of the mitophagy receptor p62, reduced lipidation of LC3B-II, and decreased expression of lysosome protein LAMP2A. These changes were regulated by PINK1/Parkin pathway and AKT/mTOR/AMPK/ULK1 signaling pathways. Importantly, we found that double treatment with nicotinamide riboside (NR) and metformin rescued mitophagy defects and mitochondrial dysfunction in POLG-mutant astrocytes. Our findings reveal that impaired mitophagy is involved in the observed mitochondrial dysfunction caused by POLG mutations in astrocytes, potentially contributing to the phenotype in POLG-related diseases. This study also demonstrates the therapeutic potential of NR and metformin in these incurable mitochondrial diseases.